Preparation and characterization of Ca1 -x La x Ti1 -x Co x O3 (0·00<x≤0·50) system - Parkash O.M.; Durga Prasad Ch.; Kumar D. (My University, 2025)
The possibility of the formation of solid solution in the system Ca1 -x La x Ti1 -x Co x O3 for x≤0·5 has been investigated. X-ray diffraction studies show that compositions with x=0·05, 0·1, 0·2, 0·3 and 0·5 prepared by the ceramic method are single-phase materials. All the compositions have a structure similar to CaTiO3 with a pseudo-cubic unit cell. Preliminary studies show that interfacial polarization contributes significantly to their dielectric constant. © 1988 Indian Academy of Sciences.